DEMOKRASI DI TENGAH TANTANGAN KEMAJEMUKAN BANGSA INDONESIA - Hanna Rahmawati, Dyah; Novriza Setya Dhewantoro, Happri (ADIDAYA : Aplikasi Pendidikan dan Sosial Budaya, 2025)
Indonesia is a country with a very high level of cultural, ethnic, and religious diversity. This makes Indonesia a social laboratory in the implementation of democracy in a multicultural society. This study aims to examine how democracy is implemented in the context of complex diversity, and to examine the challenges and strategies that can be applied to strengthen inclusive democracy in Indonesia. The method used is a literature study with a qualitative approach, which collects and analyzes scientific sources such as books, journals, and academic articles. The results of the study show that democracy and multiculturalism are two concepts that are closely related to each other in forming a just social and political order. However, in its implementation, democracy in Indonesia still faces serious challenges, such as identity politics, discrimination against minority groups, and social conflicts based on cultural or religious differences. For this reason, concrete steps are needed in the form of multicultural education that instills values of tolerance and respect for diversity, affirmative policies that guarantee fair representation, and strengthening dialogue between religions and cultures. In addition, the media and information technology also play a role in the strategy of forming public opinion and strengthening the values of multicultural democracy. This research confirms that successful democracy in Indonesia is not merely procedural democracy, but rather substantial democracy that is able to accommodate the plurality of society and build an inclusive, peaceful, and just national life.